THE MAIN ASPEKTS OF THE NATIONAL IDENTITY OF THE KOREAN DIASPORA IN UZBEKISTAN (Scientific journal of the Fergana State University, 2026)
This study is devoted to the socio-philosophical analysis of the main manifestations of the national identity of the Korean diaspora in Uzbekistan. It examines cultural and ritual traditions, language and cultural heritage, processes of social integration, and the preservation of historical memory. Special attention is given to the philosophical interpretation of the 1937 deportation experience and its role in shaping collective consciousness. It is emphasized that under globalization, the strengthening of ties with the Republic of Korea contributes to the renewal and reproduction of the diaspora’s national identity. The study concludes that the national identity of the Korean diaspora represents not only a historical and cultural heritage but also a socio-philosophical process reflecting the principle of “unity in diversity” in a multiethnic society.